Between meritocracy and ethnic discrimination: the gender difference - Mahmood Arai; Moa Bursell; Lena Nekby (Institute for the Study of Labor (IZA), 2008)
Using a two stage correspondence test methodology, this study tests employer priors against job-applicants with Arabic names compared to job-applicants with Swedish names. In the first stage, employers are sent CVs of equal observable quality. Thereafter, in the second stage, the CVs with Arabic names are given an advantage of, on average, two more years of relevant work experience. This setup allows us to test the strength of unfavorable priors against job-applicants with Arabic names and to what degree these priors are revised, on average, when resumes are enhanced. Results indicate no significant differences in call-backs for female applicants when CVs with Arabic names are enhanced. The call-back gap for men however remains large and significant despite a positive adjustment of CVs with Arabic names. This implies that negative priors against male job applicants with Arabic names are not revised by an increase in observable merits.
urn:nbn:de:101:1-2008042512
Keywords: J15; 330; Correspondence testing; ethnic discrimination; biased testing; gender; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Araber; Geschlecht; Personalbeschaffung; Schweden